Pengembangan Bahan Ajar Matematika Berbasis Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) - Nur Hidayati; Nadia Istiati (ISEJ : Indonesian Science Education Journal, 2020)
This Teaching materials have an important role in learning to support students' attractiveness in the learning process. Less attractive teaching materials used in mathematics learning, resulting in low student learning outcomes in mathematics subjects. In this study, researchers developed teaching materials for fraction material. A form of presenting independent learning materials that are arranged systematically into the smallest learning units to achieve certain learning objectives which are presented in a contextual module format in which there is a STAD type learning strategy that makes users more interactive in teaching. So that it can create a fun learning for students, and students can like mathematics. This research is a developmental research which aims to develop mathematics teaching materials through the STAD cooperative learning model on the subject of fractions. The type of research used is Research and Development research, with the research subjects of class V MI Ma'arif Rowosari. This research produces a teaching material based on the Student Teams Achievement Divisions (STAD) cooperative learning model. The results show that students are interested in the teaching materials developed for learning mathematics.